A comprehensive LC/MS analysis of novel cyclopentenedione library - Papouskova, Barbora; Bernard, Martin; Ottenschlager, Jakub; Karban, Jindrich; Velisek, Petr; Hrbac, Jan; Sykora, Jan; Storch, Jan; Vacek, Jan (Journal of pharmaceutical and biomedical analysis, 2016)
Cyclopentenediones (CPDs) are compounds with a variety of applications ranging from the preparation of functional polymers to the development of antimicrobial agents, suggesting the potential use of CPDs as novel bioactive compounds or drugs. For this reason, a detailed characterization of CPDs and the development of robust analytical methods for their trace analysis are being sought. Here we focused on the design and synthesis of a library of novelized benzylidene CPD derivatives that were consequently characterized by ultra-high performance liquid chromatography (UHPLC) on-line connected with tandem mass spectrometry (MS/MS). The library design was based on a 2-benzylidene-4-cyclopentene-1,3-dione skeleton substituted with a variety of hydroxy, methoxy, halogen, linear aliphatic, heterocyclic and saccharide moieties, primarily modulating the skeleton's hydrophobicity. The prepared CPDs were effectively ionized by positive/negative atmospheric pressure photoionization (APPI) and atmospheric pressure chemical ionization (APCI). After careful optimization of the dopant composition and flow rate, positive-mode APPI proved to be more sensitive than APCI. In negative mode, both ionization techniques gave similar results. Further, a detailed MS fragmentation study was performed, confirming the structure of the compounds and enabling positional isomers of CPDs to be differentiated on the basis of their collision spectra analysis. Finally, an optimization of the composition of the mobile phase and reversed-phased separation mode were done, followed by a selection of the most suitable UHPLC stationary phases, i.e. C18, C8 and phenyl. The applicability of the method was evaluated by the inclusion of the other two substances in the study, i.e. monomeric and dimeric bioactive CPDs, compound TX-1123 and nostotrebin 6 with cytostatic and antimicrobial activities, respectively. The results presented here could be used in further investigations of the chromatographic retention and MS behavior of CPDs, which could be utilized for their isolation, detailed characterization and analysis in biological systems.
Keywords: cyklopentany; Benzylidene Compounds; TX-1123; vysokoúčinná kapalinová chromatografie; Molecular Structure; molekulární struktura; Chromatography, High Pressure Liquid; Cyclopentanes; Atmospheric pressure ionization; benzylidenové deriváty; Mass spectrometry; tandemová hmotnostní spektrometrie; Bioactive cyclopentenediones; Nostotrebin 6; Tandem Mass Spectrometry; Liquid chromatography